DIAGNOSTIC TEST USING NEUROLOGICAL DEPRESSION DISORDERS INVENTORY FOR EPILEPSY COMPARED TO HAMILTON DEPRESSION RATING SCALE -17 AS A GOLD STANDARD - Prasetiawan, Andi; Kusumastuti, Kurnia (International Journal of Psychosocial Rehabilitation, 2020)
Background: Depression is a comorbidity that is most frequently found in epileptic patients. Epileptic patients have a 5–10 times higher risk of suffering from depression compared to the general population. Unfortunately, screening for depression hasn’t been performed routinely in outpatient neurology clinics. The Hamilton Depression Rating Scale (HDRS) is a well-known test and often used as a screening instrument, but it spares a lot of time.Objectives: To determine the diagnostic value of using the Neurological Depression Disorders Inventory (NDDI)-E compared to the HDRS-17 as a gold standard, which was used as a screening instrument to detect depression in pileptic patients.Methods: This study used a cross-sectional design on epileptic patients of the 71 patients in the neurology clinic and EEG unit at SoetomoTeaching Hospital, Surabaya, during March to June 2016. the sample in this study, consisting of 37 men and 34 women. The diagnosis of depression was performed using NDDI-E to compare with HDRS-17. Statistical analysis was performed by SPSS16 and Cat Maker.Results: Moreover, from the statistical tests obtained, the mean age was 34.3+12,301year. Compared with HDRS-17, the sensitivity value of NDDI-E was 86%, the specificity value was 72%, the positive prediction value was 67%, the negative prediction value was 89%, the positive probability ratio was 3.77%, and the negative probability ratio was 0.2.Conclusion: NDDI-E could be used as a screening instrument to detect depression in epileptic patients.